2022
DOI: 10.1101/2022.10.03.509766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced STAT5a activation rewires exhausted CD8 T cells during chronic stimulation to acquire a hybrid durable effector like state

Abstract: Rewiring exhausted CD8 T cells (TEX) towards more functional states is a major goal of cancer immunotherapy but has proven challenging due to the epigenetic stability of TEX. Indeed, TEX are epigenetically programmed by the transcription factor Tox. However, epigenetic changes continue to occur as TEX transition from progenitor (TEXprog), to intermediate (TEXint) and terminal (TEXterm) subsets, suggesting potential developmental flexibility in mature TEX subsets. By examining the transition of TEXprog into TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 85 publications
2
13
0
Order By: Relevance
“…5C). Recent literature has highlighted a role for IL-2, or more broadly Stat5a activity, in amplifying T cell populations that drive responses to checkpoint blockade ( 5759 ). Taken together, the tumor transcriptional data support the notion that Tx + αCD4 drives a robust cytotoxic T cell program leading to tumor rejection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5C). Recent literature has highlighted a role for IL-2, or more broadly Stat5a activity, in amplifying T cell populations that drive responses to checkpoint blockade ( 5759 ). Taken together, the tumor transcriptional data support the notion that Tx + αCD4 drives a robust cytotoxic T cell program leading to tumor rejection.…”
Section: Resultsmentioning
confidence: 99%
“…5C). Recent literature has highlighted a role for IL-2, or more broadly Stat5a activity, in amplifying T cell populations that drive responses to checkpoint blockade (57)(58)(59).…”
Section: Tx + ɑCd4 Leads To Cytotoxic Cd8 + T Cell Program In the Tumormentioning
confidence: 99%
“…ProjecTILs (version 2.0) was used to map our data onto scRNA-Seq data from Miller et al (45). F gsea (version 1.26.0) was used to perform GSEA on the CD8 expressing T cells using Tex gene signatures from Miller et al and Beltra(45, 59). GSVA (version 1.48.2) was used to perform GSVA on the CD8 expressing T cells using Tex gene signatures from Miller et al and Beltra et al The extent of clonal expansion per cluster was quantified using the StartracDiversity() function from scRepertoire (version 1.10.0).OT1 T cells were identified by searching the TCR repertoire for cells containing both the OT1 CDR3 Tcra amino acid sequence (CAASDNYQLIW) and the OT1 CD3R Tcrb amino acid sequence (CASSRANYEQYF).…”
Section: Methodsmentioning
confidence: 99%
“…123,124 A potential mechanism trough which IL-2 promotes differentiation of effector-like cells is through STAT5 signaling, which suppresses TOX expression, which in turn antagonizes the TOX-induced exhaustion epigenetic program, enabling the acquisition of an effector-like epigenetic landscape. 125 Additionally, IL-2 induces upregulation of the alarmin (IL-33) receptor ST-2, 123 which has been shown to promote TCF-1 expression in CD8 T cells. 126 Soluble cytokines produced in the inflammatory environment can also inhibit the differentiation of TCF1 + cells.…”
Section: Generation and Maintenance Of Tcf1 + Exhausted Subsetmentioning
confidence: 99%
“…However, a recent study showed that IL‐2 signaling through CD25 acts synergistically with checkpoint blockade by remodeling the epigenetic landscape of TCF1 + cells 123,124 . A potential mechanism trough which IL‐2 promotes differentiation of effector‐like cells is through STAT5 signaling, which suppresses TOX expression, which in turn antagonizes the TOX‐induced exhaustion epigenetic program, enabling the acquisition of an effector‐like epigenetic landscape 125 . Additionally, IL‐2 induces upregulation of the alarmin (IL‐33) receptor ST‐2, 123 which has been shown to promote TCF‐1 expression in CD8 T cells 126 …”
Section: Chronic Viral Infections and T‐cell Exhaustionmentioning
confidence: 99%